2019
DOI: 10.3906/vet-1903-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of retail egg supply chain for quality in relation to level of sanitization andfarm of origin

Abstract: In the present cross-sectional study, eggs collected from retail outlets were analyzed for physicochemical and microbial quality. Comparisons were made between "sanitized" (cleaned, sanitized, and retailed after packaging) and "unsanitized" (not subjected to cleaning, sanitization, and packaging) retail table eggs that originated from "commercial" and "backyard" (eggs retailed loose without any cleaning, sanitization, or packaging) farms. A total of 1120 eggs collected from retail markets were analyzed for phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…In contrast to Yenice et al (2016), other researchers found that conventionally produced eggs have better attributes of aroma, consistency, yolk color, flavor, and texture (Terčič et al, 2012). Even that the microbiological and dioxin counts of eggs produced under the pasture system are higher than those found in conventional eggs (Chilur Omkarappa et al, 2019;Guier-Serrano et al, 2022;Molnár & Szollosi, 2020), a situation that could affect the price in the retail market.…”
Section: Resultsmentioning
confidence: 95%

Hedonic Price of Free-Range Eggs in Costa Rica

Javier Paniagua,
Johanna Solórzano,
Barboza Navarro
et al. 2023
APSTRACT
“…In contrast to Yenice et al (2016), other researchers found that conventionally produced eggs have better attributes of aroma, consistency, yolk color, flavor, and texture (Terčič et al, 2012). Even that the microbiological and dioxin counts of eggs produced under the pasture system are higher than those found in conventional eggs (Chilur Omkarappa et al, 2019;Guier-Serrano et al, 2022;Molnár & Szollosi, 2020), a situation that could affect the price in the retail market.…”
Section: Resultsmentioning
confidence: 95%

Hedonic Price of Free-Range Eggs in Costa Rica

Javier Paniagua,
Johanna Solórzano,
Barboza Navarro
et al. 2023
APSTRACT